(untitled) (Research, Society and Development, 2022)
Objective: To verifying health risk behaviors in university students of a public institution in northeastern Brazil. Method: This cross-sectional study consisted of fifty-two (52) university students. Data were collected in October and November 2017 through the validated Youth Risk Behavior Survey (YRBS). Results: They presented normal body weight (67.3%), being (11.7%) obese and (65.4%) Sedentary. They consumed alcohol (80.8%) and 21 (40.4%) Cigarettes. The age of 17 years or more was the most frequent for the onset of alcohol consumption 27 (51.9%) and smoking 11 (21.2%). They stated that they felt safe at the university 46 (88.5%) and most 47 (90.4%) denied having been threatened or assaulted in the university environment. Conclusion: It is recognized the need for health policies in the adoption of healthier life habits for disease prevention and better quality of life among university students.